A multiscale approach for exploring bacterial transcriptional systems - Westmann, Cauã Antunes (2018)
Life is a complex phenomenon and in order to understand its underlying principles, we must be able to investigate every organizational layer that comprises it (from -omics to ecological ones). Exploring how the molecular information flows from both extra- and intracellular worlds through these layers and how they interact in the generation of phenotypic responses shall provide a more consistent background for both understanding and (re)engineering living systems. Besides, combining different approaches (in vivo and in silico) for dissecting these complex networks should allow us to achieve a more holistic and predictive view of biological phenomena. In this context, the present dissertation focus on exploring the transcriptional regulatory layer of bacteria, one of the most basal systems in gene regulation and in the integration of environmental stimuli. By merging a range of different yet complementary frameworks such as Synthetic Biology, Evolutionary Systems Biology and Metagenomics we have delved into the different aspects of this system for a more general understanding of its foundations. We have adopted the Synthetic Biology approach to explore how transcriptional logic and emergent phenomena might arise from the combinatorial architecture of complex promoters regarding the combination of specific Transcription Factor Binding Sites (TFBSs) - for the E. coli global transcription factors (TFs) Fis and IHF. Our results have shown that not only emergent phenomena might be observed in synthetic promoters, but also specific responses that resemble the dynamics of each of the individual components. Next, we have focused on applying the Evolutionary Systems framework to understand how evolutionary innovation might rise in cis-regulatory elements and what would be the main processes constraining their diversity. Our computational results based on datasets of TFBSs for three global regulators in E. coli - CRP, Fis and IHF - have pointed that transcriptional crosstalk (the sharing of TFBSs by different TFs) is ubiquitous in these systems and a key element regarding the evolution of regulatory logic and the constraining of TFBS diversity in bacteria. Lastly, we have adopted a Metagenomics approach to expand our understanding of transcriptional cis-elements beyond E. coli, by assessing and characterizing the diversity of constitutive promoters in environmental samples. These results have provided both qualitative and quantitative data regarding the natural sequence space of constitutive promoters in metagenomic libraries. In the final chapter of this dissertation, we have investigated bacterial metabolic networks, the most basal layer of molecular organization in living systems, which is deeply intertwined with transcriptional networks. Thus, we have developed a novel series of algorithms for automatic generation of stoichiometric metabolic models from (meta)genomic data, which can, in the future, be readily integrated with transcriptional data for the generation of in silico whole-cell models. Altogether, the current work has provided resourceful information regarding many aspects of transcriptional systems in bacteria which, provided the adequate theoretical framework, can be extrapolated to more complex systems such as eukaryotes. We believe this multiscale approach is fundamental for both understanding the general principles underpinning information processing in living systems and (re)engineering them for biotechnological applications.